Never Have I Ever - Shepard, Sara (Harper Teen)
Segundo libro de la serie de literatura juvenil The Lying Game, de la autora norteamericana Sara Shepard, autora del bestseller Pretty Little Liars. La serie se compone de los títulos: The Lying Game (2010), Never Have I Ever (2011), Two Truths and a Lie (2012), Hide and Seek (2012), Cross My Heart, Hope to Die (2013) y Seven Minutes in Heaven (2013).